2018
DOI: 10.18295/squmj.2018.18.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of OK-432 Therapy for the Incisionless Treatment of Head and Neck Cystic Masses: Case series

Abstract: Head and neck masses can present in different pathologies that usually vary according to the age of the patient. We report five cases of benign head or neck masses occurring among patients of different ages who were managed at the Bahrain Defence Force Royal Medical Services Hospital, Ar-Rifaa, Bahrain, between 2005-2014. All of the patients were treated using the sclerotherapeutic agent OK-432. Although surgical removal is usually considered optimal treatment in the management of such cases, OK-432 appears to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Ogita8 reported the results of OK-432 sclerotherapy in lymphangioma for the first time. In recent years, more and more articles showed OK-432 is a safe and effective treatment modality for lymphatic malformations 9. Kim evaluated 26 cases injected with OK-432 and suggested that the macrocystic type has the best effect and complete aspiration of cystic contents were important factors for success 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ogita8 reported the results of OK-432 sclerotherapy in lymphangioma for the first time. In recent years, more and more articles showed OK-432 is a safe and effective treatment modality for lymphatic malformations 9. Kim evaluated 26 cases injected with OK-432 and suggested that the macrocystic type has the best effect and complete aspiration of cystic contents were important factors for success 10.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more and more articles showed OK-432 is a safe and effective treatment modality for lymphatic malformations. 9 Kim evaluated 26 cases injected with OK-432 and suggested that the macrocystic type has the best effect and complete aspiration of cystic contents were important factors for success. 10 Aluffi Valletti et al also showed a single-center experience to management a series cases of lymphangiomas with surgery or OK-432 sclerotherapy, and they included that OK-432 therapy is a safe and effective option.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 32 included studies, there were a total of 489 patients with benign cystic lesions. Twenty patients were lost 33 2016 High Hasan 35 2018 High Kim 36 2012 Moderate Miwa 38 2007 High Woo 41 2003 High Wong 45 2017 Moderate Dool 48 2007 Moderate Kusano 50 2020 Moderate Monama 16 2010 High Watanabe 54 2002 High Taguchi 55 2005 Moderate Echavez 18 1994 High Total to follow-up and excluded from analysis, leaving 474 benign cystic lesions in 469 patients, including 5 patients with bilateral lesions. The mean duration of follow-up for all patients was 14.8 months (median, 14 months; range, 4-48 months).…”
Section: Demographicsmentioning
confidence: 99%
“… 8 , 9 The toxinproducing capacity of the bacterium is eliminated and its anticancer properties are strengthened after exposure to benzylpenicillin and heat treatment. 10 Previous studies have shown that OK-432 is effective in treating patients with various cystic diseases, including ranula, salivary mucocele, auricular hematoma, thyroglossal duct cyst and other diseases. 9 , 11 , 12 , 13 And over the past 30 years, intracapsular sclerotherapy has become the most standard therapy for LMs.…”
Section: Introductionmentioning
confidence: 99%